Cumulative social adversity as a correlate of self harm: Validity of the Reward Probability Index - Bella Magner-Parsons; Lee Hogarth (PLoS ONE, 2026)
Adversity is a risk factor for Non-Suicidal Self-Injury (NSSI). However, studies differ in their conceptualisation and indices of adversity, creating heterogeneity. The current study sought to validate the environmental adversity (ES) subscale of the Reward Probability Index (RPI) as a correlate of NSSI (and related risk factors: depression, anxiety, and impulsivity) to demonstrate the utility of this short ES questionnaire in self-harm research as a novel measure of cumulative social environmental adversity. A single, cross-sectional, online survey was completed by 149 participants, 50.3% of whom reported past year NSSI engagement. In adjusted models, environmental adversity (OR=3.8), depression (OR=1.1), low subjective socioeconomic status (SES) (OR=1.4) and indirect NSSI (OR=3.7) were associated with an increased odds of past year NSSI engagement. Pearson correlations within the NSSI subsample revealed environmental adversity, depression, and anxiety were associated with each other and NSSI, while impulsivity was not. Finally, a robust parallel mediation analysis indicated that the relationship between environmental adversity and NSSI was mediated by depression β = .165, 95%CI [.033,.336] ( R 2 = 76.87%), but not anxiety β = .017, 95%CI [−.143,.173] ( R 2 = 8.07%). These findings are consistent with empirical longitudinal and theoretical evidence proposing NSSI is associated with aversive environmental experience and depression. The finding that the environmental adversity subscale of the RPI is a valid correlate of NSSI, and is associated with other established risk factors for NSSI, validates the ES subscale for use in future longitudinal studies of NSSI as a short general assay of cumulative adversity.